A Fast Estimation Algorithm for the Direction-of-Arrival of Double Polarized Surface Arrays - Han Letian, Si Weijian, Qu Mingchao (Hangkong bingqi, 2023)
In order to solve the problem of large computation and high operation complexity in spatial spectrum estimation combined with polarization domain spectrum estimation of polarization sensitive surface array, a dimension reduction root MUSIC (Multiple Signal Classification) optimization algorithm is proposed. The received signal is processed by dimensionality reduction, and a new solution model is proposed to transform the traditional four-dimensional MUSIC into two one-dimensional root MUSIC to solve the spatial wave arrival direction, and the polarization information estimation problem of the wave signal is solved by using the spatial information and Lagrange multiplier method. Compared with the traditional 4D-MUSIC and rank deficit MUSIC, the algorithm improves the calculation speed and reduces the calculation complexity without losing the estimation accuracy, eliminates the spectrum peak search process, and eliminates the quantization error caused by the search step size. It provides a fast solution for large-scale array calculation and multiple input multiple output (MIMO) radar introduction.Simulation results show that the algorithm is effective and high precision. The spatial error of the proposed algorithm is about 0.85° at the low SNR of 0 dB, and the speed is improved by about 64.7% compared with the rank-deficient MUSIC.